A validity and reliability study of the computational thinking scales (CTS) - Korkmaz, Özgen; Çakir, Recep; Özden, M. Yaşar (Computers in human behavior, 2017)
It is possible to define Computational Thinking briefly as having the knowledge, skill and attitudes necessary to be able to use the computers in the solution of the life problems for production purposes. In this study, a scale has been developed for the purpose of determining the levels of computational thinking skills (CTS) of the students. CTS is a five-point likert type scale and consists of 29 items that could be collected under five factors. The study group of this work consists of 726 students educated at the levels of associate degree and undergraduate degree with formal education in Amasya University for the first application. For the second application 580 students who were educated in pedagogical formation education via distance education in Amasya University. The validity and reliability of the scale have been studied by conducting exploratory factor analysis, confirmatory factor analysis, item distinctiveness analyses, internal consistency coefficients and constancy analyses. As a result of the conducted analyses, it has been concluded that the scale is a valid and reliable measurement tool that could measure the computational thinking skills of the students. In addition; the digital age individuals are expected to have the computational thinking skill, and at what degree they have these skills, the revelation of whether the levels they have are sufficient or not are a requirement. Within this frame, it could be said that the scale could make significant contributions to the literature. •We aimed to develop computational thinking scale.•A 29 item computational thinking scale was composed.•Five factor were emerged for computational thinking scale.•Factors are termed Creativity, Cooperativity, Algoritmic- Critical Thinking and Problem Solving.•Reliability and validity of the scales are psychometrically good.